(untitled) (Research, Society and Development, 2021)
The purpose of this study was to analyze the critical success factors determining satisfaction (CSDFS) according to the opinion of stakeholders linked to the management of water and sanitation services in the Municipality of Pacasmayo in Peru. A non-probabilistic purposive sampling of 55 community stakeholders in the 11 central sectors and 25 civil servants was carried out. A questionnaire based on the Best - Worst Scaling (BWS) was used, which considered 16 indicators and four dimensions: Technical Aspects of Service, Quality Aspects of Service, Economic and Financial Aspects and Legal Aspects and political environment. Reliability was done with the Kuder-Richardson Coefficient (KR-20= 0.841). Scores were calculated and perceptions of both groups were compared (Mann-Whitney U Test). The exploration of the FCEDS in community stakeholders and officials highlights the importance of service quality and technical aspects, giving less interest to legal aspects and political environment, as well as economic and financial aspects. The comparison of the perceptions of both study groups did not show significant differences (p-value > 0.05). It is recommended that the levels of co-responsibility of the stakeholders involved in the management of water and sanitation services in Pacasmayo be improved and that the needs arising from the identification of the FCEDS be addressed.